The diagnostic value of C-reactive protein and adenosine deaminase biomarkers for differentiation of exudative pleural effusion - Hakani, Lira; Mitre, Anila (International Journal of Research in Medical Sciences, 2016)
Background: The aim of the present study was to investigate the roles biomarkers C-reactive protein (CRP) and adenosine deaminase (ADA) in the differentiation of exudative pleural effusion and tuberculosis from non-tuberculosis pleural effusion. Methods: The present study enrolled 150 patients with pleural effusion that were admitted to hospital between 2012- 2015. From the patients were obtained pleural fluid and serum which were administrated to test analyses within 24 hours. ADA and CRP levels were compared between the groups of exudative pleural effusion. Based on Light's criteria, biochemical, cytological etc. analyses were established the pleural effusion as exudative and the etiology of the effusion, 60 malign, 48 tuberculosis, 42 parapneumonic. Results: ADA and CRP levels differ significantly between the different groups of exudative pleural effusion but ADA ratio, pleural fluid/serum, didn’t contribute in this difference. As a better test for the difference of tuberculosis from non-tuberculosis was evaluated, ADA level in pleural fluid. Conclusions: ADA and CRP are considerable biomarker for the differences in exudative pleural effusion groups and for the difference of tuberculosis from non-tuberculosis pleural effusion. It is recommended that that other markers need to be taken into consideration to assist the results.